The Comprehensive Systematic Review of Association of Vit D Deficiency to The Prevalence of Insulin Resistance - Billy Suyanto Wijaya (International Medical Journal Corp. Ltd, 2026)
Introduction: Vitamin D deficiency has emerged as a global health concern with potential implications for metabolic health, particularly insulin resistance—a key precursor to type 2 diabetes and metabolic syndrome. Despite extensive research, the nature, strength, and causality of this association remain debated due to heterogeneous methodologies and conflicting intervention outcomes. Methods: This comprehensive systematic review synthesized evidence from 80 studies following rigorous screening and data extraction protocols. Studies were included if they examined the association between vitamin D deficiency (defined by serum 25(OH)D levels) and insulin resistance (assessed via validated methods like HOMA-IR) in adults, excluding those focused solely on supplementation, type 1 diabetes, or pregnancy. Results: The evidence consistently demonstrates a significant inverse association between vitamin D status and insulin resistance across diverse populations. Observational studies showed weak to moderate inverse correlations (r ranging from -0.134 to -0.631), with stronger associations in diabetic (pooled r ≈ -0.255) versus non-diabetic populations (pooled r ≈ -0.073) (Rafiq & Jeppesen, 2021; Alshahrani et al., 2025). Meta-analyses confirmed that higher vitamin D levels are associated with a reduced risk of type 2 diabetes (RR = 0.65) and prediabetes (RR = 0.49) (Mohammadi et al., 2021). The association was notably amplified by obesity, with correlations strengthening from r = -0.150 in normal-weight individuals to r = -0.257 in obese individuals (Rafiq & Jeppesen, 2021). However, RCTs on vitamin D supplementation yielded mixed results; while some showed improvement in insulin resistance, particularly in those with baseline glucose intolerance, others reported no significant effect in healthy or normoglycemic individuals (Mitri et al., 2011; von Hurst et al., 2009; Grimnes et al., 2011). Discussion: The relationship between vitamin D deficiency and insulin resistance is complex and modified by factors such as baseline metabolic status, BMI, and ethnicity. The discordance between strong observational associations and inconsistent interventional findings suggests that vitamin D status may be a marker of overall metabolic health and adiposity rather than a directly modifiable causal factor in all populations. Mechanistic pathways—including effects on pancreatic β-cell function, insulin receptor expression, and systemic inflammation—provide biological plausibility but underscore the influence of confounding variables. Conclusion: Vitamin D deficiency is consistently associated with a higher prevalence and severity of insulin resistance, particularly in individuals with obesity, prediabetes, or established type 2 diabetes. Maintaining adequate vitamin D status should be considered a component of metabolic health strategy. Supplementation may offer the greatest benefit for those with documented deficiency coupled with existing metabolic dysfunction, rather than as a universal preventive measure for insulin resistance.